1984
DOI: 10.1002/bbpc.19840881010
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Chemistry of Colloidal Metal Sulfides 8. Photo‐Physics of Extremely Small CdS Particles: Q‐State CdS and Magic Agglomeration Numbers

Abstract: Extremely small CdS particles were prepared in propanol−2 solution at − 78°C and in aqueous solution in the presence of sodium hexametaphosphate at room temperature. These colloids are colorless. Their UV absorption spectra exhibit several maxima. Aging of the colloids is accompanied by intensity variations in the absorption maxima and by a shift of the onset of absorption to longer wavelengths. These small CdS particles hardly possess semiconductor properties (Q‐state CdS). A semi‐classical treatment of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(148 citation statements)
references
References 16 publications
11
137
0
Order By: Relevance
“…27 Brus and co-workers suggested that sulfur vacancies, located at the surface of the material, might be important in mediating low-energy emissions. There are several reasons for this, one of which is the considerable size of 48. The excitonic transition shifts to higher energy values along with an increase in the molar absorption coefficient, as the particle size decrease.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…27 Brus and co-workers suggested that sulfur vacancies, located at the surface of the material, might be important in mediating low-energy emissions. There are several reasons for this, one of which is the considerable size of 48. The excitonic transition shifts to higher energy values along with an increase in the molar absorption coefficient, as the particle size decrease.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…The idea that negatively charged nanoparticles can agglomerate to form larger particles via magic-number progression was proposed in ref. 4 , and in 1987 he explained the stability of polydisperse superspheres containing a few tens of nanoscale particles in terms of the balance between long-range electrostatic repulsion and short-range attractive dispersion forces 6 . In the early 1990s Zukoski and co-workers also explored how equilibrium between long-and short-range forces influenced the size of nanoparticle clusters 7,8 .…”
mentioning
confidence: 99%
“…[ 78 ] The conversion between radius and volume relied on the assumption that the clusters are approximately spherical. The absorption spectrum of a population of magic clusters formed in the absence of excess ligand was found to be composed -as in the system of Henglein and coworkers, [ 6 ] and others [ 76 , 79 , 80 ] -of multiples of a monomer cluster. Furthermore, the absorption from the larger clusters increased at the expense of the smaller clusters as the reaction progressed.…”
Section: Progress Reportmentioning
confidence: 94%